Impact of Accounting Digitalization on MSME Performance and Sustainability - Yunia Oktari; Rini Novianti; Tri Anggraeni (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This research addresses the limited understanding of how digital transformation contributes to MSME performance and sustainability by examining the roles of digital accounting systems, accounting software adoption, and financial management practices. The study introduces an integrative model that positions sustainability as a mediating variable, offering a novel perspective beyond traditional efficiency-based approaches. The primary objective is to evaluate the direct and indirect effects of digitalization and financial practices on MSME outcomes. A quantitative approach was employed, using survey data collected from MSMEs in Tangerang, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital accounting systems and accounting software adoption have significant positive effects on both performance and sustainability, while financial management practices exhibit a weaker, indirect influence through sustainability. These results demonstrate that digitalization enhances not only operational effectiveness but also long-term business resilience. The study contributes to the literature by emphasizing the strategic role of sustainability in linking digital tools to improved business outcomes. It offers practical implications for policymakers and MSME stakeholders seeking to strengthen competitive advantage in the digital economy through targeted digital adoption strategies. Keywords: Accounting Digitalization; Digital Transformation; MSME Competitiveness; MSME Performance; Technology Adoption